Inverted Bilayered Opal Photoanodes for Dye Sensitised Solar Cells - Kamba, E. A.; Yerima, E. A.; AttahDaniel, E. B. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
Developing efficient photoanode materials remains a major challenge in improving the performance of dye-sensitized solar cells (DSSCs). This study aims to fabricate and evaluate a bilayer photoanode comprising potassium titanate (K₂Ti₄O₉) nanobelts coupled with a zinc oxide (ZnO) inverse-opal structure and to investigate the effects of electrolyte cation identity and concentration on DSSC performance. K₂Ti₄O₉ nanobelts were synthesized through a solid-state reaction between potassium carbonate (K₂CO₃) and titanium dioxide (TiO₂) and subsequently integrated with the ZnO inverse-opal layer. Photocurrent–voltage measurements were conducted using a two-electrode DSSC configuration containing an I₃⁻/I⁻ redox electrolyte. The devices were illuminated using a 300 W xenon arc lamp equipped with an AM 1.5G filter at an intensity of 100 mW cm⁻². The findings show that the ZnO inverse-opal/K₂Ti₄O₉ bilayer system achieved a photoelectric conversion efficiency of 1.19%, exceeding the 1.04% efficiency obtained using the single K₂Ti₄O₉ system. This improvement indicates that the ZnO inverse-opal layer contributes substantially to device performance by functioning as a photonic-crystal underlayer. The study demonstrates the potential of integrating ZnO inverse-opal structures with K₂Ti₄O₉ nanobelts to enhance DSSC photoanode performance and provides a basis for developing bilayered photonic architectures for solar-energy conversion.